Feather bedding and childhood asthma associated with house dust mite sensitisation: a randomised controlled trial. Issue 6 (30th March 2011) - Glasgow, Nicholas J; Ponsonby, Anne-Louise; Kemp, Andrew; Tovey, Euan; van Asperen, Peter; McKay, Karen; Forbes, Samantha
Abstract : Introduction: Observational studies report inverse associations between the use of feather upper bedding (pillow and/or quilt) and asthma symptoms but there is no randomised controlled trial (RCT) evidence assessing the role of feather upper bedding as a secondary prevention measure. Objective: To determine whether, among children not using feather upper bedding, a new feather pillow and feather quilt reduces asthma severity among house dust mite (HDM) sensitised children with asthma over a 1-year period compared with standard dust mite avoidance advice, and giving children a new mite-occlusive mattress cover. Design: RCT. Setting: The Calvary Hospital in the Australian Capital Territory and the Children's Hospital at Westmead, Sydney, New South Wales. Patients: 197 children with HDM sensitisation and moderate to severe asthma. Intervention: New upper bedding duck feather pillow and quilt and a mite-occlusive mattress cover (feather) versus standard care and a mite-occlusive mattress cover (standard). Main outcome measures: The proportion of children reporting four or more episodes of wheeze in the past year; an episode of speech-limiting wheeze; or one or more episodes of sleep disturbance caused by wheezing; and spirometry with challenge testing. Statistical analysis included multiple logistic and linear regression. Results: No differences between groups were found for primary end points – frequent wheeze (OR 1.51, 95% CI 0.83 to 2.76, p=0.17), speech-limiting wheeze (OR 0.70, 95% CI 0.32 to 1.48, p=0.35), sleep disturbed because of wheezing (OR 1.17, 95% CI 0.64 to 2.13, p=0.61) or for any secondary end points. Secondary analyses indicated the intervention reduced the risk of sleep being disturbed because of wheezing and severe wheeze to a greater extent for children who slept supine. Conclusion: No differences in respiratory symptoms or lung function were observed 1 year after children with moderate–severe asthma and HDM sensitisation were given a mite-occlusive mattress cover and then received either feather upper bedding (pillow and quilt) or standard bedding care.